A unique case of thoracic endometriosis syndrome and pulmonary Langerhans’ cell histiocytosis: Six recurrent pneumothoraces - Varun Gupta; Ka-Won Noh; Hansjörg Maschek; Stefan Thal; Stefan Welter (Respiratory Medicine Case Reports, 2022)
Spontaneous pneumothorax (SP) in women of reproductive age with causes such as thoracic endometriosis syndrome (TES) presents a diagnostic and therapeutic challenge. A 33-year-old women was treated conservatively with chest tube insertion for a first occurrence of a right-sided pneumothorax in September 2015. In January 2016, a right-sided video-assisted thoracoscopic surgery (VATS) wedge resection and partial parietal pleurectomy was performed due to a recurrence. A right-sided VATS was again performed in December 2016 with multiple wedge resections and a total pleurectomy revealing a pulmonary Langerhans’ cell histiocytosis (PLCH) in the histological and immunohistochemical examinations. The patient was recommended an abstinence of smoking and further course was unremarkable until May 2019, when due to a recurrent pneumothorax, she received a talc pleurodesis via right-sided VATS. Due to yet another recurrence, she underwent a talc slurry pleurodesis over a right sided chest drain. In March 2020 due to recurrence, a right-sided VATS was performed and a blueish nodular lesion was resected from the diaphragm. The histological examination revealed an endometriosis with a diagnosis of TES. Since the patient did not exhibit a temporal relationship between her periods and the onset of pneumothorax symptoms, a final diagnosis of non-catamenial endometriosis-related pneumothorax was made. The patient is currently continuing smoking abstinence and is under hormone therapy. She has not presented with a recurrence. In clinical practice, it is important not to just relay on the information available to us, but to reevaluate the patient history to uncover new clues leading to a new diagnosis.